Decentralisation, security consolidation and territorial peacebuilding: is Colombia about to close the loop?. Issue 6 (1st November 2016) - Schultze-Kraft, Markus; Valencia, Oscar; Alzate, David
Abstract: In November 2016, the Colombian Government and the insurgent FARC signed a final peace agreement. Central to the accord is what the parties call 'territorial peacebuilding', a long-term strategy to integrate Colombia's vast (rural) hinterlands into the nation's legal political system and economy. 'Territorial peacebuilding' follows on from decentralisation and security consolidation, both of which experienced problems, however, ultimately falling short of integrating Colombia. To be more effective now it is imperative to devise a governance strategy for territorial peacebuilding that includes the subnational political and administrative entities, enhances citizen participation and protects local governments from capture by criminal interests.